INCREASING TEACHER CREATIVITY THROUGH STRENGTHENING ACHIEVEMENT MOTIVATION AND INFORMATION LITERACY - Rizki Amarullah Alqorni; Eka Suhardi; Rita Retnowati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This study aims to increase teacher creativity. The approach applied is a correlational approach and SITOREM analysis. The implementation of this research was carried out at public elementary schools in Cibungbulang District. With a population of 166 teachers and a sample of 117 teachers, this sample was selected using the proportional random sampling method. Furthermore, the methods used in this research are survey methods and data analysis techniques, with correlation tests and simple linear and multiple linear regression tests. The results of the research that has been carried out the show: 1. there is a significant positive relationship between the variables Achievement Motivation (X1) and Teacher Creativity (Y) with ry1 = 0.714. 2. There is a significant positive relationship between Information Literacy (X2) and Teacher Creativity (Y) variables with ry2 = 0.529. 3. there is a positive and significant relationship between the variable Achievement Motivation (X1) and Information Literacy (X2) together with Teacher Creativity (Y) with ry12 = 0.723. So it means that Teacher Creativity can be increased through Achievement Motivation and Information Literacy.